The Concentration and Stability of Drug Activity in Seattle, Washington Using Police and Emergency Medical Services Data - Hibdon, Julie (Journal of quantitative criminology, 2017)
Objectives Prior research demonstrates that crime is highly concentrated at place and that these concentrations are stable from year to year, highlighting the importance of place to crime control and prevention. A potential limitation is that most studies only use one data source to diagnose these patterns. The present study uses data from both police and emergency medical services (EMS) to explore the spatial concentration and stability of drug activity in Seattle, Washington from 2009 to 2014. Methods We use concentration graphs and group-based trajectory analysis to examine concentration and stability of calls related to drug activity in both data sources separately and combined. Additionally, we employ Andresen’s S-Index to determine the similarity of concentration within the SPD data, the EMS data and the combined data year to year as well as the degree of co-location between the SPD and EMS data during the study period. Results We find a high degree of concentration and group-based stability for both SPD and EMS drug calls across all street segments in Seattle. Conversely, we find only moderate local geographic stability of drug use across street segments as indicated by each of the data sources over the study period. Last, we find the spatial patterns in drug use as indicated by each data source are significantly different each year. Conclusions At the same time these findings provide support for the law of crime concentration, they also raise questions about local stability patterns. Additionally, they highlight the importance of expanding inquiries of crime and place research into new data sources. Our results serve to reinforce the importance of multiple data sets in quantifying, understanding, and responding to the drug problem in Seattle.